INFLUENCE OF SHOPPING LIFESTYLE, DISCOUNT AND FASHION INVOLVEMENT ON IMPULSIVE BUYING OF SHOPEE ONLINE SHOPPING - Fransischa Veronika Claudya Titing; Frederik G. Worang; Merinda H. C. Pandowo (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2022)
Consumptive behavior arises besides being due to meeting diverse needs, but also to follow the growing trend in the market. Therefore, marketers must be able to understand the desires and needs of these consumers, as well as the trends of the millennial generation that are in effect in order to create and develop their marketing strategies in the era of revolution. This research is intended to find out and analyze the influence between shopping lifestyle, discount and fashion involvement as independent variable towards impulse buying as dependent variable to the Shopee customer. This study used the quantitative research by spreading questioners to the customer of Shopee who shop about 120 persons. The sample was taken by the purposive sampling method. The measurement of variable used the Likert scale with the weight scale from 1 to 5. To find out the effect of X variable towards Y variable used Multiple Linear Regression analysis. The result from this research found that there is a significant influence between discount and fashion involvement toward impulsive buying on Shopee fashion product. It also means that discount and fashion involvement simultaneously influence to impulsive buying. However, the result also shows that there is no significant influence in shopping lifestyle on impulsive buying of Shopee fashion product.